SERVICE PROVISION AND DEVELOPMENT IN AGRICULTURE - MURTAZAEV OLIM,; IBRAGIMOV GAYRAT ABLAQULOVICH,; KHURRAMOV AZIZBEK MUKHIDDIN UGLI, (International Journal of Innovations in Engineering Research and Technology, 2021)
Many factors for influence an agricultural enterprise’s efficiency, one of them is access to potential services. This article describes and analyzes various methods of organizing services, as well as its role, importance, and ways of improving it. We analyze agricultural service provision contract value and value covering, reasons of problems for payments, agricultural development.